When fate meets its maker : bidirectional effects between beliefs in anthropomorphic God and fate - Yuen, Wei Lun (2018)
Past studies have shown that fate and belief in God are strongly associated. However, finer-grained investigations into this association have been lacking. The current research sought to highlight the key role anthropomorphic perceptions of God plays in this association, as well as demonstrate the bidirectional causal effects between beliefs in an anthropomorphic God and fate. In Study 1, participants reminded of an anthropomorphic God were found to have stronger fate beliefs than participants primed with other non-anthropomorphic entities. Study 2 examined the reverse causal flow, and showed that experimentally inducing inclinations toward fate beliefs elicited strong religiosity among the participants. Additionally, Study 2 also shed light on specific anthropomorphic qualities that were essential for the causal effect of fate beliefs on religiosity. Specifically, while anthropomorphic perceptions of other entities’ mental world typically follow two dimensions, agency and experience, perceiving God to possess agency was crucial for fate beliefs to increase one’s belief in God. Taken together, findings across both studies illustrated the bidirectional causality between beliefs in fate and God, and showed that anthropomorphic perception of God was imperative to the aforementioned effects. Implications of the findings were also discussed.